Scapular resting posture and scapulohumeral rhythm adaptations in volleyball players: implications for clinical shoulder assessment in athletes - Pascoal, Augusto Gil (2023)
Volleyball players develop shoulder sports-related adaptations due to repetitive overhead motions. It is essential to differentiate between these sports-related adaptations and pathological patterns in clinical assessments, particularly on scapular resting posture and scapulohumeral rhythm. Using an electromagnetic tracking system, the 3D shoulder kinematics of 30 male elite asymptomatic volleyball players and a matching control group were recorded at rest and in eight humeral elevation positions, in 15-degree increments from 15 to 120 degrees. The results indicated that the dominant scapular resting posture of the volleyball group was more anteriorly tilted than the control group (Volleyball: mean = −12.02°, STD = 4.16°; Control: mean = −7.45°, STD = 5.42°; Mean difference = 4.57°; STD = 6.85°; CI95% = 2.1° to 7.1°). The scapulohumeral rhythm in the volleyball group showed greater scapular internal rotation (Volleyball: mean = 41.60°, STD = 9.14°; Control: mean = 35.60°, STD = 6.03°; mean difference = 6.02°, STD = 1.47°; CI95% = 4.80° to 7.25°) and anterior tilt (Volleyball: mean = −9.10°, STD = 5.87°; mean = −2.3°, STD = 9.18°; mean difference = 6.88°, STD = 0.66°; CI95% = 6.34° to 7.43°). These findings suggest that volleyball players have developed a sports-related scapular adaptive pattern. This information may be valuable for clinical assessment and rehabilitation planning in injured volleyball players and may aid in the decision-making process for determining a safe return-to-play after a shoulder injury.